HUBUNGAN PERILAKU TEMAN SEBAYA DENGAN KESETARAAN SOSIAL SISWA KELAS V SDN KELEYAN 1 BANGKALAN - Nurjannah, Intan; Laili, Aulia Rohmatin Nur; Yusuf, Irsyadah; Putri, Pinky Violine Agustin; Ashidiqi, Ahmad Hasbi; Pratikno, Ahmad Sudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the discovery of social inequality in the relationshipbetween students at Elementary School of Keleyan 1 Bangkalan. Some studentsexhibit less positive behaviors, such as choosing certain friends, forming groupsbased on gender, and giving ridicule to peers. This study aims to determine therelationship between peer behavior and social equality of grade V students ofElementary School of Keleyan 1 Bangkalan. This study uses a quantitativeapproach with a type of correlational research. The sampling technique used wassaturated sampling, so that all 21 students in class V were used as researchsamples. Data collection techniques are carried out through questionnaires,interviews, and documentation. The research instrument uses a Likert scale withfour answer choices. Data analysis was carried out using Pearson's ProductMoment descriptive analysis and correlation test with the help of the SPSSapplication. The results showed that peer behavior was in the high category with apercentage of 66.70%, while students' social equality was in the high category with a percentage of 61.90%. The results of the normality test showed that the datawas normally distributed and the results of the linearity test showed that therelationship between the two variables was linear. The results of Pearson'sProduct Moment correlation test obtained a correlation coefficient value of 0.556with a significance value of 0.009 < 0.05. Thus, it can be concluded that there is apositive and significant relationship between peer behavior and social equality ofgrade V students of SDN Keleyan 1 Bangkalan.